The Phenomenon of Colonialism in Africa: Contending Theoretical Perspectives - Wabah, Goodnews; N-ue, Uebari Samuel (NIU Journal of Humanities, 2020)
This paper examines the contending theoretical perspectives of colonialism which violently spread into Africa in the last quarter of the nineteenth century. Colonialism has posed a daunting challenge to researchers and scholars on the use of theoretical perspectives to scholarly investigate, analyze, evaluate and interpret its phenomenon, nature and fundamental principles. Using the diverse historical methods and combine evidence, this paper traces the bases of colonialism to two distinct and opposing intellectual groups. The first group is the Eurocentric school of thought which tries to explain the rationale behind the colonization of Africa from mainly European viewpoints. In this category are the Economic necessity, Marxist theory of economic exploitation, technological superiority, civilizing mission, social Darwinism, social atavism and national pride and prestige perspectives. The second group is the Africa dimension Theorists. While trying to debunk the claims of the Eurocentric theorists, African school of thought contends that the historical events which occurred in Africa prior to the nineteenth century contributed largely to the subjugation and conquest of Africa. The paper argues for the use of integration of theories, paradigms and perspectives in historical scholarship for a meaningful narrative. Keywords: Colonialism, Phenomenon, Theory, Perspectives, Paradigms, Africa and Historical Scholarship.